ANALISIS KEBUTUHAN PENGEMBANGAN ANGKUTAN KHUSUS KARYAWAN PADA PUSAT PEMERINTAHAN KOTA DENPASAR DI LUMINTANG - Oktariani, Ni Pt. Emmy; Suthanaya, P. Alit; Suparsa, I G. Putu (JURNAL SPEKTRAN; Vol. 3, No. 1, Januari 2015, 2015)
Abstract : Employee transportation service is one of the traffic management method that imitate carpooling system which can decrease the used of private vehicle  that being use towards the centers of activity with employee transportation services. The purpose of this research are to analyze socio – economic characteristic, operational system, vehicle operating cost and cost reduction. This research was conducted in Lumintang Denpasar. The method that was used in this research include field survey such us questionnaire spreading to the respondent and also doing a direct interview to the related parties. Result of the analysis indicated that the majority of employee’s (88,47%) used motorcycle with average travel distance of 5 km’s, 4 employee transportation routes were planned with time cycle between 23 to 58 minutes , headway between 2 to 10 minutes and employee transportation operational cost is between Rp.252.531 to Rp.270.241 every day. operational expense saving with total Rp. 8110.332.019 and fuel saving as much as 6.624 liters a year
Keywords: Employee Transportation Services, Operational System, Vehicle Operating Cost, Cost Reduction